2005
DOI: 10.1021/jp050580s
|View full text |Cite
|
Sign up to set email alerts
|

Strong Green Emission from α-SiAlON Activated by Divalent Ytterbium under Blue Light Irradiation

Abstract: This contribution reports on luminescence properties of divalent ytterbium in alpha-SiAlON at room temperature. Ytterbium-doped alpha-SiAlON powders, with the compositions of (M(1-2x/v)Yb(x))(m/v)Si(12-m-n)Al(m+n)O(n)N(16-n) (M = Ca, Li, Mg, and Y, v is the valency of M, 0.002 < or = x < or = 0.10, 0.5 < or = m = 2n < or = 3.5), were synthesized by sintering at 1700 degrees C for 2 h under 0.5 MPa N2. A single, intense, broad emission band, centered at 549 nm, is observed due to the electronic transitions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
91
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 21 publications
5
91
0
Order By: Relevance
“…Since it is not necessary for β-SiAlON to accommodate the metal ions for charge compensation, rare-earth ions have been confirmed to locate in the continuous channel by electron microscopy [16] or Pr 3+ ), which provide more options for the use in white LEDs [7,11], [17][18][19]. Doping these rare-earth ions into β-SiAlON host lattice also can obtain optimal PL properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is not necessary for β-SiAlON to accommodate the metal ions for charge compensation, rare-earth ions have been confirmed to locate in the continuous channel by electron microscopy [16] or Pr 3+ ), which provide more options for the use in white LEDs [7,11], [17][18][19]. Doping these rare-earth ions into β-SiAlON host lattice also can obtain optimal PL properties.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Eu 2+ , Yb 2+ commonly exhibits 4f-5d fluorescence. Xie et al [17] reported strong green emission in Yb 2+ -doped α-SiAlON arising from the 4f 14 -4f 13 5d interconfigurational transitions of Yb 2+ . In contrast to Yb 2+ -doped fluorides, sulfates and phosphates [22][23][24], this longer-wavelength emission is contributed by the nitrogen-rich location of Yb 2+ that leads to the combination of strong crystal-field splitting of the 5d states of Yb 2+ and high covalent bonding (nephelauxetic effect) between Yb 2+ and (O, N).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports describing the development of phosphors [7][8][9][10][11][12][13][14][15][16] for violet chips, which have an external quantum efficiency that is intrinsically higher than that of blue chips [17][18][19] . A pc-LED with a violet chip generates white light only from the luminescence of the phosphors.…”
mentioning
confidence: 99%
“…Another example is given by the green emitting material aSiAlON doped with Yb 2? [138]. In this case, the doping ion shows luminescence spectra due to 4f 14 $ 4f 13 5d 1 interconfigurational transitions [139].…”
Section: Green Phosphors-other Hostsmentioning
confidence: 90%
“…The excitation spectrum was monitored at k em = 549 nm and the emission spectrum was recorded at k ex = 342, 300, and 445 nm. Both figures are adapted from [138] Top Curr Chem (Z) (2016) (with doping in the region of 2 %) has been considered by Do et al [143]. Samples were prepared by NaBr-aided solid state reaction in flowing H 2 S. Excitation at 455 nm yields a broad symmetric emission band in the range 500-625 nm, whose maximum is red shifted from 535 to 555 with increasing x (moving from SrGa 2 S 4 to CaGa 2 S 4 ).…”
Section: Green Phosphors-other Hostsmentioning
confidence: 99%